Broadband optical quantum memory - Reim, K (2011)
This thesis is about the experimental implementation of a high-speed and robust quantum memory for light. A novel far off-resonant Raman approach to ensemble-based quantum memories in a room-temperature environment is developed and demonstrated. Storage and retrieval of sub-nanosecond, weak coherent light pulses at the single-photon-level with total efficiencies exceeding 30% and storage times of up to 4 μs are achieved. The coherence of the memory is shown by directly interfering a copy of the incident signal with the retrieved signal from the memory. The unconditional noise floor of the memory is found to be low enough to operate the memory in the quantum regime at room temperature. Multiple readout of a single stored excitation is demonstrated, suggesting that 100% readout is possible in different temporal modes. Furthermore, first results regarding the storage and retrieval of polarisation encoded qubits are obtained. This and the memory’s ability to operate in the quantum regime at room temperature with a low unconditional noise floor illustrate its potential usefulness for real world applications.